Greater financial toxicity relates to greater distress and worse quality of life among breast and gynecologic cancer survivors. Issue 1 (19th August 2021) - Benedict, Catherine; Fisher, Sophie; Schapira, Lidia; Chao, Sabrina; Sackeyfio, Sarah; Sullivan, Tara; Pollom, Erqi; Berek, Jonathan S.; Kurian, Allison W.; Palesh, Oxana
Abstract: Background: Financial toxicity includes distress and burden from cancer‐related costs. Women are more likely to experience worse cancer‐related financial outcomes than men. This study evaluated breast and gynecologic cancer patients' subjective experiences of financial toxicity and associations with distress and quality of life (QOL). Methods: A cross‐sectional survey study included measures of financial toxicity (Comprehensive Score for Financial Toxicity [COST] Version 2), distress (Patient Health Questionnaire), and QOL (Functional Assessment of Cancer Therapy). Chi‐square, t ‐tests, and ANOVAs examined bivariate relationships. Two regression models tested associations between financial toxicity and distress and QOL, controlling for covariates. Financial toxicity subgroups were compared based on a validated grading system. Results: Participants ( N = 273; 74% breast cancer) averaged 54.65 years (SD = 12.08), were 3.42 years (SD = 4.20) post‐diagnosis, and 33% reported cancer‐related change in employment status. Financial toxicity was "mild" overall (COST M = 26.11, SD = 11.14); 32% worried about cancer‐related financial problems ( quite a bit/very much ; item‐level analysis). Worse financial toxicity related to younger age ( p < 0.001), identifying as a non‐Asian minority ( p = 0.03) or Hispanic ( p = 0.01), being single ( p < 0.001), lower education ( p = 0.004), lower income ( p < 0.001), late‐stage disease ( p = 0.001), recurrent disease ( p = 0.004), and active treatment ( p < 0.001). In separate multivariable models, greater financial toxicity related to greater distress ( β = −0.45 p < 0.001) and worse QOL ( β = 0.58, p < 0.001). Financial toxicity subgroups reported clinically significant differences in distress and QOL ( p 's < 0.05). Conclusions: Cancer‐related financial burden is associated with pervasive negative effects and may impact subgroups differently. Future research should explore financial experiences across subgroups, aiming to better identify those at risk and build targeted interventions.